(untitled) (Perioperaciina Medicina, 2024)
Adequate perioperative pain relief is an integral part of anesthesia. Opioid analgesics occupy one of the key places in the purchase of acute and chronic pain in the world. The article presents current data on the clinical effectiveness of remifentanil, a derivative of fentanyl, which is a selective ultra-short-acting μ-opioid receptor agonist when used in the perioperative period for the treatment of acute and chronic pain. Comparisons of the therapeutic activity and physicochemical properties, pharmacokinetic and pharmacodynamic characteristics of remifentanil with other opioids (fentanyl, sufentanil, alfentanil) are provided. Its unique properties (eg, organ function-independent metabolism, non-accumulation, rapid onset of action, and short duration of action) distinguish it from other opioid agents. Remifentanil is at least as effective as comparator opioids such as fentanyl, sufentanil in relieving pain and sedating patients during the perioperative period. In addition, it provides rapid and predictable extubation and is associated with shorter duration of mechanical ventilation and shorter length of hospitalization than comparators in some studies. In addition, remifentanil is well tolerated in both adults and children. Thus, remifentanil is a desirable addition to currently available pharmacologic agents used to treat period pain in patients